Impacts of the 2016/17 food insecurity response program on maize prices in Malawi - Baulch, Bob; Gondwe, Anderson; Chafuwa, Chiyembekezo (International Food Policy Research Institute, 2018)
In early 2016, Malawi suffered its second consecutive year of harvest failure. An emergency was declared in April 2016 and the resulting humanitarian response, known as the Food Insecurity Response Program (FIRP), was of unprecedented scale: almost 40 percent of the population received in-kind food or cash transfers (or both) at an estimated cost of US$ 287 million. Yet despite the extensive nature of the response, prices for the main food staple, maize, stayed relatively ‘flat’ throughout most of the year and then declined during the pre-harvest lean season. This paper examines this paradox, focusing on why in-kind food distribution did not depress maize prices while cash transfers did not raise them. Using daily information on maize prices, and food and cash transfers from ten major markets during the height of the FIRP, we employ time series methods to analyze the properties of the series and model the formation of maize prices using autoregressive distributed lag models.